Funkcjonowanie spółdzielczego sektora bankowego w Polsce po akcesji Polski do Unii Europejskiej - Gniewek, Józefa (Functioning of the Co-Operative Banking Sector in Poland after the Accession of Poland to the EU, 2005)
The paper presents functioning of the cooperative bank sector in Poland in 2001-2003. The financial analysis shows that cooperative banks are growing up slowly but systematically. The economic indicators show, that many of them are much worse in Poland than in other European countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 237-241